2016
DOI: 10.1016/j.jenvman.2016.08.065
|View full text |Cite
|
Sign up to set email alerts
|

Physical-chemical evaluation of hydraulic fracturing chemicals in the context of produced water treatment

Abstract: Produced water is a significant waste stream that can be treated and reused; however, the removal of production chemicals-such as those added in hydraulic fracturing-must be addressed. One motivation for treating and reusing produced water is that current disposal methods-typically consisting of deep well injection and percolation in infiltration pits-are being limited. Furthermore, oil and gas production often occurs in arid regions where there is demand for new water sources. In this paper, hydraulic fractur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 100 publications
0
38
0
Order By: Relevance
“…Chemical disclosure is widely recognized as a fundamental prerequisite for the open and transparent analysis of the hazards and risks associated with chemicals [2,4,10,27,45,46]. Previous studies have shown that many oil and gas field chemicals are not expected to have negative environmental or health impacts, but that some compounds, including surfactants, biocides, and corrosion inhibitors may be harmful to the environment, and that in many cases there is insufficient information to confidentially evaluate the potential environmental impact of chemicals that are used in significant amounts on oil and gas fields [19–24,47,48]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical disclosure is widely recognized as a fundamental prerequisite for the open and transparent analysis of the hazards and risks associated with chemicals [2,4,10,27,45,46]. Previous studies have shown that many oil and gas field chemicals are not expected to have negative environmental or health impacts, but that some compounds, including surfactants, biocides, and corrosion inhibitors may be harmful to the environment, and that in many cases there is insufficient information to confidentially evaluate the potential environmental impact of chemicals that are used in significant amounts on oil and gas fields [19–24,47,48]. …”
Section: Resultsmentioning
confidence: 99%
“…Compounds reported by CASRN mostly had corresponding mass-usage information, important for risk analysis, but 97 did not have toxicity profiles in the public databases used in this study (Table 2; S3 Table). Altogether, 70% of the chemical additives reported in the SCAQMD could not be fully evaluated using data-based hazard analysis approaches [20,21,47], suggesting that current reporting requirements may need to be strengthened, if the regulatory objective includes generating data needed for risk assessments.…”
Section: Resultsmentioning
confidence: 99%
“…3, 34 The reason for this change in clay-control strategy is not known and may be inconsequential from a risk management perspective, but in the absence of publicly available information on the toxicity, biodegradability, or other environmentally critical properties of clay control agents, it may be premature to dismiss risk from these materials altogether. 3-5, 43 Twenty of the newly identied chemicals were chlorinated, brominated, or iodated aromatic hydrocarbons (Table S-1 †). Halogenated aromatic compounds can be environmentally persistent and toxic, so there is specic interest in the use of these types of compounds in the context of produced water reuse and risk assessment.…”
Section: Well Stimulation Treatmentsmentioning
confidence: 99%
“…Sustainability is an appealing label attached to all sectoral economies despite the wide range of uncertainties, loopholes, and hidden side-effects that may occur in any real production system. Circular economy (CE) is probably the most provocative pathway to rethinking, redesigning [1], reducing, reusing [2], recycling [3], and recovering resources used by different sectors of the economy [4]. Reframed in this context, farming is all about managing the growth processes of plants and animals sustainably, and one mandatory input in these processes is water.…”
Section: Introductionmentioning
confidence: 99%